Revisiting Polyarenes and Related Molecules: An Update of Synthetic Approaches and Structure‐Activity‐Mechanistic Correlation for Carcinogenesis. Issue 6 (21st February 2018) - Sar, Dinabandhu; Kim, Benjamin; Ostadhossein, Fatemeh; Misra, Santosh K.; Pan, Dipanjan
Abstract: A major proportion of basic cause for human cancer has been linked to widespread environmental pollutants including analogs of polyarenes. Search of an effective therapy can be started with the understanding of the generation of such "carcinogens" and their biological interactions. This review is to discuss the syntheses, structural activities, mechanistic and biological studies of polyarenes such as polycyclic aromatic hydrocarbons (PAHs), polycyclic azaarenes (PAAs) and their thia‐analogs (PASH). It also summarizes the mechanism of mutagenicity and tumorigenicity via metabolic interventions producing diol epoxide complexes and eventually formation of DNA adducts. It suggests that inhibition of oxidative reactions and formation of diols and epoxides and unspecific intracellular activation of cytochrome P450 enzymes could be approaches in therapy against such mutagenicity and tumorigenicity. Thus, this review reflects that understanding of molecular mechanisms and activations along with a clinical and translational medicine approach would require achieving both prevention and treatment of this atrocity. Abstract : Polyarenes and related molecules exert carcinogenicity through the formation of dihydrodiol and diolepoxide